2018
DOI: 10.1371/journal.pone.0201180
|View full text |Cite
|
Sign up to set email alerts
|

If it doesn’t help, it doesn’t hurt? Information elaboration harms the performance of gender-diverse teams when attributions of competence are inaccurate

Abstract: Information elaboration—the act of exchanging, discussing, and integrating information and perspectives through verbal communication—tends to be considered as the silver bullet that drives the performance of diverse teams. We challenge this notion by proposing that the effect of information elaboration on team performance depends on the accuracy of within-group competence attributions, i.e. the extent to which attributions of task competence among team members correspond with members’ actual task competence. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 80 publications
(160 reference statements)
0
11
0
Order By: Relevance
“…The findings of Chatman et al. (2008) and van Dijk et al. (2018) provide preliminary evidence that gender role expectations shape interactions and performance at the group level.…”
Section: Advancing Research On the Group-level Consequences Of The Flmentioning
confidence: 74%
See 4 more Smart Citations
“…The findings of Chatman et al. (2008) and van Dijk et al. (2018) provide preliminary evidence that gender role expectations shape interactions and performance at the group level.…”
Section: Advancing Research On the Group-level Consequences Of The Flmentioning
confidence: 74%
“…If such women and men in reality are the most competent group members, we argue that their limited influence in the group is likely to harm the group’s performance. In line with this argument, a recent study showed that gender-diverse groups tended to perform worse to the extent that less-competent members were more influential (van Dijk et al., 2018). We thus argue that the performance of a work group decreases the more the behavior of target women and men is based on inaccurate gender role expectations.…”
Section: The Consequences Of the Flywheel Of Gender Role Expectationsmentioning
confidence: 81%
See 3 more Smart Citations